Physician recruitment of patients to non-therapeutic oncology clinical trials: ethics revisited - Lee eBlack; Gerald eBatist; Denise eAvard; Caroline eRousseau; Zuanel eDiaz; Bartha Maria Knoppers (Frontiers Media S.A., 2013)
Tailoring medical treatment to individual patients requires a strong foundation in research to provide the data necessary to understand the relationship between the disease, the patient, and the type of treatment advocated for. Non-therapeutic oncology clinical trials studying therapeutic resistance require the participation of patients, yet only a small percentage enroll. Treating physicians are often relied on to recruit patients, but they have a number of ethical obligations that might be perceived as barriers to recruiting. Concepts such as voluntariness of consent and conflicts of interest can have an impact on whether physicians will discuss clinical trials with their patients and how patients perceive the information. However, these ethical obligations should not be prohibitive to physician recruitment of patients-precautions can be taken to ensure that patients' consent to research participation is fully voluntary and devoid of conflict, such as the use of other members of the research team than the treating physician to discuss the trial and obtain consent, and better communication between researchers, clinicians and patients. These can ensure that research benefits are maximized for the good of patients and society.